Minutes of the International Committee (extract)
028-0184-001 EXTRACT FROM MINUTES OF INTERNATIONAL COMMITTEE MEETING. SEPTEMBER 22, 1936. 54. POSITION IN SPAIN. A circular notice was submitted from the I.F.T.U., stating that in agreement with the L.S.I and the Socialist Party of Spain, a Spanish Committee of the International Solidarity Fund had been set up in Madrid for the organisation of relief work. Notice was also read of the convocation of an emergency meeting of the I.F.T.U. General Council, for Monday, 28th September, 1936, for the purpose of discussing further methods of assisting the Spanish workers in their struggle. It is intended to propose that public meetings should be held in Paris, Brussels and London, the one in Paris to be arranged on the evening of Monday, September 28, after the General Council meeting, and the one in London towards the end of the week, if possible. The suggestion was made that at the London meeting a Spanish comrade should speak. IT WAS AGREED TO RECOMMEND that at the Paris General Council meeting a suggestion be made that a strong deputation should be sent to the Spanish T.U.C, at Madrid, as a gesture of sympathy and support. It was also suggested that the Foreign Office might be approached in regard to the attitude of Portugal, as referred to in the Congress resolution. In regard to the proposed public meeting in London, the view was expressed that this should be run under the auspices of the National Council of Labour, who at their meeting fixed for Wednesday, September 30, would be guided by the report of the I.F.T.U. General Council meeting. 292/946/28/184